INFLUENCE OF BIOFEEDBACK IN PATIENTS WITH SEQUELAE OF STROKE - Pimentel, Tatiana dos Anjos; Silva, Bruna Carla Pereira da; Silva, Cláudia Kelly Vieira; Souza, Juliana de Oliveira; Januário, Priscila de Oliveira; Cruz, Ariela Torres (Journal of Health Care, 2017)
Introduction: Stroke is considered the main neurological impairment that causes functional disability in adults. Several rehabilitation techniques, such as Biofeedback therapy, have been inserted to therapeutic modalities to stimulate the motor functions of these patients. Objectives: To evaluate the effect of Biofeedback on patients with sequelae of stroke. Materials and methods: Clinical, randomized, double-blind study on 16 individuals divided into two groups: experimental (EG) and control (CG). EG participants underwent 16 medical services, two times a week, using Biofeedback and were assessed by goniometry to measure range of motion (ROM) of wrist flexion and extension before, after and one month after the end of the treatment. CG participants were assessed at the same time. Results: We found that in EG there was an increase of ROM of wrist extension right after (p=0.0151) and one month after the end of the treatment (p=0.0227), and there was no statistically significant results for the analysis of flexion motion of EG and CG. When comparing groups, we observed no difference between them. Conclusions: The proposed treatment proved to be effective for increasing the ROM of wrist extension of EG participants; however, there was no statistical difference between the groups analyzed.
Keywords: Stroke; biofeedback; muscle spasticity; paresis